Digital Déjà vu: The Enduring Presence of Gender Stereotypes in Memes - Athoi, Adhra Sreoshi (SCHOLARS: Journal of Arts & Humanities, 2024)
Memes are a crucial cultural unit for exploring and understanding the dynamics of the digital society in which examining the gender balance is a key pathway for measuring where it states. It is very important for any social science researcher to read and see if the new generation is rewriting the sexist behavior composed by the culture over the past ages and that too in a platform, which is extensively dominated by them. Hence, the main purpose of this study is to explore gender communication and gender construction in new media through memes. The study was conducted by analyzing 152 memes collected from Facebook. Theoretically it attempts to read gender from a gender-constructionist perspective. Thematic analysis was used as the method of going through these memes and the major themes were pointed out and an overall analysis was presented. The main finding from the analysis is that despite the expectation of progressive views, memes continue to reinforce traditional gender stereotypes, with a predominant focus on men narrating content that perpetuates established roles, overshadowing limited challenges to patriarchal norms. This study attempts to decode the influence of memes as cultural artifacts on the portrayal and reinterpretation of gender roles in the digital era. By scrutinizing the interplay between the new generation's expressions and prevailing cultural norms, the study unravels the transformative potential of memes in reshaping societal attitudes towards gender.